Bytový dům v Humpolci - Novák, Tomáš (Vysoké učení technické v Brně‎, Antonínská 548/1, 601 90 Brno, http://www.vutbr.cz/, 2018)
The bachelor thesis deals with the design of an apartment building with a bicycle shop in the town of Humpolec. The thesis contains complete documentation for the execution of the construction, assessment in terms of building physics and fire safety report. The building is divided into two operational units. The first unit is a bicycle shop, which includes staff facilities and bicycle service facility. The second unit consists of individual apartments and their facilities. In the basement, there are cellars for each apartment, a technical room and a workshop. On the ground floor, there is a accessible flat for handicapped persons in size 2 rooms plus kitchen corner. The second floor consists of four apartments two available in size of 1 room plus kitchen corner and two size of which is 2 rooms plus kitchen corner. On the last third utility floor, there are two apartments size of which is 3 room plus kitchen corner which is layout designed for a 4-5 member family. The house have masonry system, where the vertical structures on the underground floor are made of concrete block cast by concrete. Overground vertical structures are made of Porotherm clay blocks. Horizontal constructions are made of pre-stressed Spiroll ceiling panels. The roof is cold roof and its supporting structure consists of timer truss girder mounted on the perimeter walls.
Keywords: bicycle shop; partial basement; dokumentace pro provádění stavby; Apartment building; příhradové vazníky; documentation for the execution of the contruction; Bytový dům; částečné podsklepení; three above ground floor; jedno podzemní podlaží; zděný systém; pre-stressed panels Spiroll; prodejna kol; one underground floor; bachelor thesis; tři nadzemní podlaží; truss girder; bakalářská práce; masonry system; Humpolec; předpjaté panely Spiroll